GLACIOLOGICAL RESEARCH PROGRAM IN EAST QUEEN MAUD LAND, EAST ANTARCTICA PART 6 ADVANCE CAMP, 1985 - KIKUCHI, Tokio; AGETA, Yutaka (National Institute of Polar Research, 1987)
P(論文) departmental bulletin paper